Effect of conservation agriculture on soil organic and inorganic carbon sequestration and lability: A study from a rice–wheat cropping system on a calcareous soil of the eastern Indo‐Gangetic Plains. (18th February 2020) - Dey, Abir; Dwivedi, Brahma Swaroop; Bhattacharyya, Ranjan; Datta, Siba Prasad; Meena, Mahesh Chand; Jat, Raj K.; Gupta, Raj Kumar; Jat, Mangi Lal; Singh, Vinod Kumar; Das, Debarup; Singh, Ravi G.
Abstract: Increasing soil carbon (C) in arable soils is an important strategy to achieve sustainable yields and mitigate climate change. We investigated changes in soil organic and inorganic carbon (SOC and SIC) under conservation agriculture (CA) in a calcareous soil of the eastern Indo‐Gangetic Plains of India. The treatments were as follows: conventional‐till rice and wheat (CT‐CT), CT rice and zero‐till wheat (CT‐ZT), ZT direct seeded rice (DSR) and CT wheat (ZT‐CT), ZTDSR and ZT wheat without crop residue retention (ZT‐ZT), ZT‐ZT with residue (ZT‐ZT+R), and DSR and wheat both on permanent beds with residue (PB‐PB+R). The ZT‐ZT+R had the highest total SOC in both 0–15 and 15–30 cm soil layers (20% and 40% higher ( p  < .05) than CT‐CT, respectively), whereas total SIC decreased by 11% and 15% in the respective layers under ZT‐ZT+R compared with CT‐CT. Non‐labile SOC was the largest pool, followed by very labile, labile and less labile SOC. The benefits of ZT and residue retention were greatest for very labile SOC, which showed a significant ( p  < .05) increase (~50%) under ZT‐ZT+R compared with CT‐CT. The ZT‐ZT+R sequestered ~2 Mg ha −1 total SOC in the 0–15 cm soil layer in 6 years, where CT registered significant losses. Thus, the adoption of CA should be recommended in calcareous soils, for C sequestration, and also as a reclamation technique.